Address challenges created by COVID‐19 pandemic. Issue 1 (8th February 2021) - Hope, Joan
Abstract : The COVID‐19 pandemic has created challenges for registrars and enrollment professionals. Speakers at a session at the American Association of Collegiate Registrars and Admissions Officers Strategic Enrollment Management Conference described what they have experienced at their institutions and how they have addressed problems to enroll students and keep them on track to graduate.